La calidad del servicio y el nivel de satisfacción de los clientes de Cineplanet Trujillo Centro. - Valencia Venegas, Daysi Margarita (2011)
The present research work graduated with a title THE QUALITY of the SERVICE And THE LEVEL OF SATISFACTION OF THE CUSTOMERS OF CINEPLANET TRUJILLO CENTER; It has like fundamental purpose to evaluate CINEPLANET's quality of service TRUJILLO; Taking like base general themes on quality, the customer, the service and the satisfaction of the customer; As well as the model SERVQUAL. Research work used the fact-finding descriptive transverse design, as well as the following methods: Deductive inductive, analytical synthetic method, the statistician and the fact-finding techniques as he interviews her, you poll them and the list of comparisons. In opinion polls the applied for to CINEPLANET's customers TRUJILLO CENTER highlighted reliability and confiablidad like one of the aspects most important frequently of empathy, response capacity or responsibility, certainty and tangibilidad as well as interviews the applied for to the staff we can highlight that workers get around inside a labor favorable and friendly weather, with scarce conflicts due to inefficient communications. In this thesis, each question of the questionnaire was analyzed and they represented themselves in graphic way, stops at a later time to group them according to the dimensions of the quality of service elaborating also your respective graphics. These results were the base for the formulation of the findings and general recommendations of this research work.